Enzyme Supplementation of Commercial Feed Diluted with Copra Meal for Laying Hens - Mael, Sandy Hoffman; Diarra, Siaka Seriba; Devi, Ashika (Indian Journal of Animal Nutrition, 2019)
The study investigated the effect of enzyme supplementation of commercial feed diluted with copra meal in laying hens. Two hundred 126 d old Shaver Star-Cross pullets were fed commercial feed alone or diluted with 2 levels (20 and 30%) of copra meal (CM) with or without enzyme in 4 replicates of 10 birds each. Feed intake, hen-day production and egg quality measurements formed the response criteria. Results showed no significant differences (P < 0.05) among the treatments in terms of feed intake, hen-day production, egg weight, egg mass and FCR (feed: egg). Egg surface area was lower on the control compared to the dilution diets (P < 0.05). There were no effects of diet on egg shell thickness, Haugh unit and yolk colour (P > 0.05). Eggs produced on the control had higher shape index compared to the 30% CM without enzyme (P < 0.05). Cost of the kg feed reduced linearly with the dilution. Feed cost per unit egg produced was lower on 30% dilution with enzyme compared to the 20% without (P < 0.05). In conclusion, diluting commercial feed with CM up to 30% does not compromise egg production and egg quality traits. This will reduce production cost and add value to CM. There is need for more research into higher rates of dilution, enzyme source and concentration.